Injectable light-cured dual-network hydrogel as well as preparation method and application thereof
By using the photocrosslinking technology of composite hydrogel with methacrylylated gelatin and hyaluronic acid in bone regeneration materials, a dual network structure is formed, and the problem of fast degradation speed and insufficient induction ability of gelatin materials is solved, and the problem of gelatin materials is achieved. Effective regeneration and repair of bone tissue.
Patent Information
- Application Number
- CN202310795465.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing gelatin-based materials have fast degradation speed and poor mechanical properties in bone regeneration, which cannot be used for a long time. The carrier materials have insufficient ability to induce osteogenesis and differentiation of cells, making it difficult to effectively promote the repair of bone tissue.
Complex hydrogels using methacrylated gelatin and methacrylated hyaluronic acid form a dual network structure through blue light irradiation, combining with the photocrosslinking of OGP, achieving long-term slow release of OGP and forming good biocompatibility and injectable photocurable hydrogels that induce cell osteogenesis differentiation ability.
The hydrogel promotes cell proliferation and migration in vitro, effectively promotes the regeneration and repair of bone defect areas in vivo, and provides a stable bone regeneration treatment plan.
Smart Images

Figure HDA0004314870890000011 
Figure HDA0004314870890000012 
Figure HDA0004314870890000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedicine, and specifically relates to an injectable photocurable double-network hydrogel for bone regeneration, and a preparation method and application thereof. Background Art
[0002] Every year, many people suffer from bone tissue defects due to trauma or disease. Autologous bone transplantation and allogeneic bone transplantation are common traditional methods for treating bone defects. However, their practical applicability is often limited due to the scarcity of autologous bone and immune rejection of allogeneic bone. To solve these problems, tissue engineering provides more possibilities for the regeneration and repair of bone tissue. Simply put, three-dimensional scaffolds loaded with active growth factors and cells can achieve efficient bone tissue repair by releasing active ingredients and mimicking the structural morphology and repair process of tissues. Among them, gelatin, as a hydrolyzate of natural collagen, contains many active functional groups such as amino, carboxyl and hydroxyl groups, and has good biocompatibility and low antigenicity. In particular, gelatin has many cell-specific binding sites, such as matrix metalloproteinase (MMP) sensitive degradation sites and Arg-Gly-Asp (RGD) sequences, which can promote cell adhesion, migration and differentiation. However, gelatin has a fast degradation rate and poor mechanical properties, and needs to be chemically modified. Currently, gelatin is modified with methacrylic acid to form methacrylated hydrogel (GelMA), but GelMA is still a relatively unstable material that degrades quickly even in the absence of cells and cannot be used for a long time. Therefore, further research and development is needed. Summary of the invention
[0003] The purpose of the present invention is to provide an injectable light-curable double-network hydrogel for bone regeneration, which has suitable physical properties and biocompatibility and has good ability to induce cell osteogenic differentiation.
[0004] In a first aspect of the present invention, there is provided an injectable photocurable composite hydrogel, wherein the composite hydrogel is obtained by mixing methacryloyl gelatin and methacryloyl hyaluronic acid and then irradiating the mixture with blue light.
[0005] In another preferred embodiment, the mass ratio of the methacryloyl gelatin to the methacryloyl hyaluronic acid is 1-10:1.
[0006] In another preferred embodiment, the mass ratio of the methacryloyl gelatin to the methacryloyl hyaluronic acid is 2-8:1, preferably 3-6:1, and more preferably 5:1.
[0007] In another preferred embodiment, the wavelength of blue light is 400-450 nm, and the cross-linking time is 10-50 seconds.
[0008] In another preferred embodiment, the wavelength of the blue light is 400-420 nm, preferably 405 nm.
[0009] In another preferred embodiment, the cross-linking time is 20-40 seconds, preferably 30 seconds.
[0010] The second aspect of the present invention provides an injectable photocurable OGP-loaded composite hydrogel, wherein the OGP-loaded composite hydrogel comprises the composite hydrogel described in the first aspect and OGP, wherein the OGP is graft-copolymerized in the composite hydrogel by photocrosslinking.
[0011] In another preferred embodiment, the OGP is methacryloylated osteogenic growth peptide (OGP-MA).
[0012] The third aspect of the present invention provides a method for preparing the composite hydrogel according to the first aspect, the preparation method comprising the following steps:
[0013] i) dissolving methacryloyl gelatin (GelMA) and methacryloyl hyaluronic acid (HAMA) in deionized water or phosphate buffer containing lithium acylphosphonate (LAP) to obtain a GelMA / HAMA mixed solution;
[0014] ii) using blue light to irradiate the GelMA / HAMA mixed solution to obtain the composite hydrogel.
[0015] In step i, the concentration of the GelMA solution is 1wt%-20wt%, the concentration of the HAMA solution is 0.5wt%-10wt%, and the concentration of the LAP is 0.05wt%-1wt%.
[0016] In another preferred embodiment, the concentration of the GelMA solution is 5wt%-15wt%, preferably 10.0wt%.
[0017] In another preferred embodiment, the concentration of the HAMA solution is 1 wt%-5 wt%, preferably 2 wt%.
[0018] In another preferred embodiment, the concentration of LAP is 0.1wt%-0.5wt%, preferably 0.2wt%.
[0019] In another preferred embodiment, the wavelength of blue light is 400-450 nm, and the cross-linking time is 10-50 seconds.
[0020] In another preferred embodiment, the wavelength of the blue light is 400-420 nm, preferably 405 nm.
[0021] In another preferred embodiment, the cross-linking time is 20-40 seconds, preferably 30 seconds.
[0022] The third aspect of the present invention provides a method for preparing the OGP-loaded composite hydrogel according to the second aspect, the preparation method comprising the following steps:
[0023] a) dissolving methacryloyl gelatin (GelMA) and methacryloyl hyaluronic acid (HAMA) in deionized water or phosphate buffer containing lithium acylphosphonate (LAP) to obtain a GelMA / HAMA mixed solution;
[0024] b) mixing the GelMA / HAMA mixed solution with the osteogenic growth peptide, and stirring in a dark environment to obtain a composite hydrogel precursor;
[0025] ii) using blue light to irradiate the composite hydrogel precursor to obtain the OGP-loaded composite hydrogel.
[0026] In another preferred embodiment, the OGP is methacryloylated osteogenic growth peptide (OGP-MA).
[0027] In another preferred embodiment, in step i, the concentration of the GelMA solution is 1wt%-20wt%, the concentration of the HAMA solution is 0.5wt%-10wt%, and the concentration of the LAP is 0.05wt%-1wt%.
[0028] In another preferred embodiment, the concentration of the GelMA solution is 5wt%-15wt%, preferably 10.0wt%.
[0029] In another preferred embodiment, the concentration of the HAMA solution is 1 wt%-5 wt%, preferably 2 wt%.
[0030] In another preferred embodiment, the concentration of LAP is 0.1wt%-0.5wt%, preferably 0.2wt%.
[0031] In another preferred embodiment, the concentration of OGP is 0.01wt%-0.2wt%.
[0032] In another preferred embodiment, the concentration of OGP is 0.02wt%-0.1wt%, preferably 0.05wt%.
[0033] In another preferred embodiment, the wavelength of blue light is 400-450 nm, and the cross-linking time is 10-50 seconds.
[0034] In another preferred embodiment, the wavelength of the blue light is 400-420 nm, preferably 405 nm.
[0035] In another preferred embodiment, the cross-linking time is 20-40 seconds, preferably 30 seconds.
[0036] The fifth aspect of the present invention provides use of the composite hydrogel described in the first aspect for preparing a cell culture carrier, a drug carrier or a bone repair material.
[0037] The sixth aspect of the present invention provides the use of the OGP-loaded composite hydrogel described in the second aspect for preparing a bone repair material.
[0038] In another preferred embodiment, the OGP-loaded composite hydrogel is used to prepare bone defect filling materials.
[0039] The GelMA / HAMA double network hydrogel loaded with OGP provided by the present invention realizes effective long-term slow release of OGP based on the combination of physical chain entanglement and chemical cross-linking effect. The hydrogel polymer is rapidly formed under illumination, and has suitable porous structure, physical properties and biocompatibility. In in vitro experiments, GelMA / HAMA-OGP hydrogel is conducive to cell proliferation, adhesion and migration, upregulates osteogenesis-related genes and protein expression, and has good in vitro ability to induce cell osteogenic differentiation. In in vivo animal experiments, the hydrogel promotes regeneration and repair of bone defect areas. The preparation process of the present invention is simple, cheap and easy to obtain, and the double network hydrogel can be prepared by relatively simple steps, which provides a new idea for bone regeneration treatment.
[0040] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Each feature disclosed in the specification can be replaced by any alternative feature that provides the same, equal or similar purpose. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 SEM image of the hydrogel.
[0042] Figure 2 It shows that after 30 seconds of blue light irradiation, liquid GelMA / HAMA-OGP (left) can quickly transform into a gel-like solid (right).
[0043] Figure 3 The hydrogel was shown to have injectable properties.
[0044] Figure 4 The rheological test results are shown.
[0045] Figure 5 The swelling ratio test results are shown.
[0046] Figure 6 Degradability test results are shown.
[0047] Figure 7 This is the cumulative release curve of OGP.
[0048] Figure 8 Live / dead cell staining results are shown.
[0049] Fig. 9 The results of osteogenic differentiation assay are shown.
[0050] Fig.10 The composite hydrogel was shown to be capable of bone regeneration. DETAILED DESCRIPTION
[0051] The inventors of the present application have developed a GelMA / HAMA double network hydrogel through extensive and in-depth research, which is rapidly formed under illumination, has a suitable porous structure, physical properties and biocompatibility, is loaded with OGP, and achieves effective long-term slow release of OGP based on the combination of physical chain entanglement and chemical cross-linking effect. In in vitro tests, GelMA / HAMA-OGP hydrogel is conducive to cell proliferation, adhesion and migration, upregulates osteogenesis-related gene and protein expression, and has good in vitro ability to induce cell osteogenic differentiation. In in vivo animal experiments, the hydrogel promoted the regeneration and repair of bone defect areas. On this basis, the present invention has been completed.
[0052] the term
[0053] Gelatin Methacryloyl (GelMA)
[0054] Gelatin is a hydrolyzed product of natural collagen, which is modified with methacrylic acid to form methacrylated hydrogel (GelMA). However, GelMA is still a relatively unstable material and degrades rapidly even in the absence of cells.
[0055] Hyaluronic Acid Methacryloyl (HAMA)
[0056] Hyaluronic acid (HA) is a ubiquitous component of the extracellular matrix and can interact with many cell surface receptors, such as cell adhesion molecules (CD44) and intracellular adhesion molecule-1 (ICAM-1), showing good biocompatibility and bioactivity. The carboxyl and hydroxyl groups of HA are chemically modified by methacrylate to form cross-linked HA methacryloyl (HAMA) hydrogels under UV irradiation, which further improves its chemical and mechanical properties and provides greater rigidity and high levels of viscoelasticity. However, HA-based hydrogels are not conducive to cell adhesion, which hinders cell proliferation.
[0057] Osteogenic Growth Peptide (OGP)
[0058] Osteogenic growth peptide (OGP) is a natural molecule containing a highly conserved 14-amino acid motif. It has been shown to effectively promote osteoblast proliferation, differentiation, alkaline phosphatase activity and matrix mineralization, and can promote bone formation and increase trabecular bone density by regulating the expression of transforming growth factors (TGFs), insulin-like growth factors (IGFs) and basic fibroblast growth factor (bfgf) in the body. Moreover, the amino acid sequence of OGP extracted from human serum is exactly the same as that of OGP in rats and mice, and has homology with most animals, showing that the structure of OGP is evolutionarily conserved.
[0059] Biological scaffolds alone do not have satisfactory osteoinductive ability. One of the focuses of tissue engineering is to study how to associate growth factors with biological scaffolds to enhance their osteoconductivity and osteoinductivity. Currently, most studies focus on delivering OGP by physical adsorption or self-assembly. However, OGP is very sensitive to the surrounding environment and can be easily degraded by non-covalent attachment to the scaffold surface.
[0060] The inventors unexpectedly discovered that by photo-crosslinking, OGP graft copolymerization in GelMA / HAMA double network hydrogel can achieve long-term effective release of OGP, and is beneficial to cell proliferation, adhesion and migration, upregulates osteogenesis-related genes and protein expression, and has good in vitro ability to induce cell osteogenic differentiation. In in vivo animal experiments, the hydrogel promoted the regeneration and repair of bone defect areas. The injectable photo-crosslinked double network composite hydrogel of the present invention encapsulates OGP and can achieve in situ bone regeneration.
[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not indicated in the following examples are usually performed under conventional conditions (such as the conditions described in Sambrook et al., Molecular Cloning: Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989)) or according to the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and weight parts.
[0062] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.
[0063] Example 1
[0064] 1.1 Preparation of GelMA / HAMA double network hydrogel
[0065] The frozen polypolymers of GelMA and HAMA (Mw = 12-14 kDa, StemEasy, China) were completely dissolved in PBS (pH = 7.4) containing phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) (0.2 wt%) under magnetic stirring at 50 °C. The final concentrations of the polymers were 10 wt% and 2 wt% (w / v), respectively. The solution was cured by irradiation with 405 nm blue light for 30 s to obtain GelMA / HAMA double network hydrogel.
[0066] 1.2 Preparation of OGP-loaded GelMA / HAMA double network hydrogel
[0067] The frozen prepolymers of GelMA and HAMA (Mw = 12-14 kDa, StemEasy, China) were completely dissolved in PBS (pH = 7.4) containing phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP) (0.2wt%) under magnetic stirring at 50°C, and the final concentrations of the polymers were 10wt% and 2wt%, respectively. Methacryloylated osteogenic growth peptide (OGP-MA) (MA-YGFGG, Qiangyao Company, China) was added and stirred under light-proof conditions to obtain a composite hydrogel precursor. The solution was cured by irradiating with 405nm blue light for 30 seconds to obtain an OGP-loaded composite hydrogel (GelMA / HAMA-OGP).
[0068] Example 2
[0069] Characterization of composite hydrogels
[0070] Morphology
[0071] Scanning electron microscopy (SEM, Hitachi TM4000Plus, Japan) was used to examine the morphology of GelMA / HAMA and GelMA / HAMA-OGP hydrogel scaffolds at an accelerating voltage of 15 kV. The samples were dehydrated in gradient ethanol and treated with 2.5% glutaraldehyde before freeze-drying for SEM. Platinum was sputtered onto the surface of the scaffolds before SEM examination. There were three samples in each group. Five images were randomly selected from each sample.
[0072] like Figure 1As shown, the morphology of the hydrogels was observed by scanning electron microscopy, and there was no obvious difference in the internal structure of the double network hydrogel and the double network hydrogel loaded with OGP. This shows that we encapsulated the OGP protein in the double network hydrogel without changing its structure. These hydrogel materials have appropriate pore sizes, which are 53.7±3.88μm and 58.6±4.15μm, respectively. They provide favorable physical conditions for three-dimensional cell growth and material exchange. Therefore, GelMA / HAMA-OGP hydrogels allow for the sustained release of OGP protein, cell entry and adhesion, internal and external circulation of nutrients, and the outflow of metabolic waste.
[0073] Further, the porosity of the hydrogel was determined by the ethanol displacement method. The initial weight W0 and initial volume V0 of the sample were recorded. The sample was soaked in anhydrous ethanol for 5 minutes. After removal, the residual ethanol was wiped off the surface of the sample and the weight W1 was recorded. The density of ethanol is ρ. The porosity was calculated as follows: Porosity (%) = (W1-W0) / ρV0×100% (n=3).
[0074] The porosity of GelMA / HAMA and GelMA / HAMA-OGP hydrogels was 68.2% and 66.7%, respectively. There was no significant difference between the two groups. Appropriate porosity facilitates material exchange and is a necessary characteristic of ideal biomaterials.
[0075] Gelation
[0076] Gelation was demonstrated using a tabletop technique. Briefly, the physical state of the hydrogel samples in the vials was tested by rotating the vials, replicating the effect of injecting the hydrogels in situ into the body at physiological temperatures. Figure 2 As shown in the figure, after 30 seconds of blue light irradiation, the liquid GelMA / HAMA-OGP can be quickly transformed into a gel-like solid. Based on the above findings, GelMA / HAMA-OGP hydrogel is effective for rapid shaping.
[0077] Injectability
[0078] To evaluate the injectability of the hydrogel, GelMA / HAMA-OGP hydrogel was added to a syringe and passed through an 18-gauge needle. Extrude to observe the extrusion status. Figure 3 As shown, the shear thinning behavior of the hydrogel proves that it has excellent injectability and can pass smoothly through an 18-gauge needle, making it convenient for clinical injection operations.
[0079] Rheological properties
[0080] The rheological properties of the hydrogels were studied using a rheometer (MCR92, Anton Par) to observe the changes in viscosity with temperature, shear force, and frequency.-1 The viscosity characteristics are examined at a shear rate of 10°C to 60°C. The temperature sweep test measures the viscosity in a temperature range of 10°C to 60°C. The fluctuations of the storage modulus (G') and loss modulus (G) with frequency (ω; rad / s) allow observation of the frequency sweep.
[0081] like Figure 4 As shown in Figure a, the viscosity curve of the hydrogel changes linearly at room temperature and is independent of temperature, and the production conditions are more stable. By increasing the temperature, the fluidity of the hydrogel increases significantly, facilitating the injection operation.
[0082] like Figure 4 As shown in Figure 2(b), these hydrogel solutions show a similar decreasing trend with increasing shear rate and are viscous in the low shear rate range. -1 or higher, the viscosity dropped drastically, indicating that they are injectable and malleable, which facilitates bone repair operations during treatment.
[0083] like Figure 4 As shown in Figure c, the storage modulus (G') and loss modulus (G") of GelMA / HAMA and GelMA / HAMA-OGP hydrogels tend to be stable within the scanning range. Within the frequency range, the storage modulus is higher than the loss modulus, indicating that the network structure of the hydrogel maintains a stable gel state within the entire test range.
[0084] Expandability
[0085] The swellability of hydrogels is closely related to their network structure, mechanical strength, and ability to control the transport of cellular nutrients and metabolites and absorb body fluids.
[0086] To investigate the swelling ratio of GelMA / HAMA and GelMA / HAMA-OGP hydrogels, they were weighed after freeze drying and the initial weight was indicated as W0. The dried hydrogel samples were then immersed in PBS at room temperature for 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, and 8 h. The mass of the wet hydrogel was recorded at each time point Wt. The swelling ratio (SR) was calculated as: SR = (Wt-W0) / W0×100%.
[0087] Figure 5 The swelling curves showed that GelMA / HAMA and GelMA / HAMA-OGP hydrogels almost reached a balanced swelling state after being immersed in PBS for 5 h, and the swelling ratios were 22.5±1.9% and 21.6±0.5%, respectively.
[0088] Degradability
[0089] The degradability of the hydrogel is an important physical and biological property for maintaining the stability of the scaffold. To evaluate the degradation rate of GelMA / HAMA and GelMA / HAMA-OGP hydrogels, they were weighed after freeze drying and marked with the initial weight W0. The freeze-dried samples were immersed in PBS at room temperature for 1d, 2d, 4d, 7d and 14d, then freeze-dried, weighed and marked with the weight Wt. The degradation ratio (DR) was calculated as: DR = (W0-Wt) / W0×100%.
[0090] like Figure 6 As shown, the in vitro degradation experiment showed that after incubation in PBS for 14 days, the degradation rates of the hydrogels were 65.7±1.6% and 62.6±4.1%, and the degradation trends were very similar.
[0091] Release
[0092] In order to draw the release curve of OGP in the hydrogel material, the GelMA / HAMA double network hydrogel loaded with OGP was immersed in 5 ml of PBS at 37°C. The immersion supernatant of GelMA / HAMA-OGP hydrogel was collected at 1, 2, 3, 4, 5, 7 and 14 days. The total protein level was measured using the BCA protein concentration detection kit (Solarbio, China). The cumulative release rate (%) of OGP at different time points = (the cumulative release amount of aspirin at the corresponding time point / the total amount of aspirin in the material) * 100%.
[0093] like Figure 7 The cumulative release curve showed that the initial burst release of OGP occurred within 24 hours, accounting for about 18% of the total. The initial burst release was able to effectively stimulate cell proliferation and differentiation in the bone defect area. The release of OGP protein was observed for up to 14 days, which was due to the synergistic effect of physical encapsulation and chemical interlocking of the double network hydrogel, which ensured the sustained release of the drug. Over time, the release rate of OGP gradually slowed down, and the cumulative release of OGP was about 70% at 14 days, indicating that GelMA / HAMA-OGP hydrogel has the characteristics of sustained release and provides a stable drug delivery system. The slow release of OGP is conducive to maintaining the effective concentration of extracellular drugs in the scaffold, fully and persistently promoting the regeneration and repair of bone tissue.
[0094] Cell viability
[0095] Cell counting kit-8 (CCK-8, Solarbio, China) was used to detect cell viability. MC3T3-E1 cells were suspended in complete culture medium (α-MEM medium supplemented with 10% serum and 1% penicillin-streptomycin mixture) and 1×10 3Cells were seeded into 96-well plates at a density of 10 cells / 100 μL. After 24 hours of culture, the blank control group (NC group), GelMA / HAMA and GelMA / HAMA-OGP groups replaced the culture medium and continued to culture. The blank group was cultured with complete culture medium, the GelMA / HAMA hydrogel group was the control group, and the cells were co-cultured with GelMA / HAMA hydrogel, and the GelMA / HAMA-OGP hydrogel group was the experimental group, and the cells were co-cultured with GelMA / HAMA-OGP hydrogel. After 1d, 3d, 5d and 7d of culture, 100 μL of culture medium containing 10 μL of CCK-8 staining solution was added to each well. The culture plate was cultured in an incubator at 37°C and 5% carbon dioxide humidity for two hours (Thermo Fisher Scientific, USA). Then, the absorbance intensity at 450nm was detected using a microplate spectrometer (Tecan, Switzerland). The absorption intensity of light is proportional to the number of cells. Live / dead staining was performed using a live / dead viability / cytotoxicity kit (Beyotime, China), and the results were shown in Figure 8 As shown in the figure above.
[0096] The density is 1×10 3 The MC3T3-E1s suspension was seeded in a 24-well tissue culture plate and cultured for 24 hours. After 3 days of culture, live / dead cell staining assay was performed. 250 μl of Calcein AM / PI detection working solution was added to each well. Incubated at 37°C in the dark for 30 minutes. Images were then taken using an inverted fluorescence microscope (Nikon, Japan). The results are shown in Figure 2. Figure 8 As shown in the figure below.
[0097] The above experiments demonstrated the biosafety of GelMA / HAMA-OGP hydrogels through CCK-8 and live-dead staining experiments. There were no significant differences among the three groups, and the cells in all three groups increased over time. The experimental results showed that the GelMA / HAMA-OGP composite hydrogel has great biocompatibility and biosafety. Calcein AM / PI staining was used to distinguish live cells from dead cells. Most of the stained cells were alive and green in color, with only a few red fluorescent spots appearing. In addition, most of the cells showed a polyhedral morphology, which indicates that MC3T3-E1 can survive, spread and adhere well to the gel surface, and the hydrogel composite material provides a suitable biological microenvironment.
[0098] Osteogenic differentiation potential
[0099] MC3T3-E1 cells were cultured, and the blank group was treated with osteogenic induction medium (α-MEM medium supplemented with 10% serum, 1% penicillin-streptomycin mixture, 2mM L-glutamine, 1.8mM KH 2 PO4 , 100 μM L-ascorbic acid sodium phosphate, 10 nM dexamethasone sodium phosphate), the GelMA / HAMA hydrogel group was the control group, and the cells were co-cultured with GelMA / HAMA hydrogel in osteogenic induction medium, and the GelMA / HAMA-OGP hydrogel group was the experimental group, and the cells were co-cultured with GelMA / HAMA-OGP hydrogel in osteogenic induction medium. The osteogenic differentiation potential of MC3T3-E1 in hydrogel materials was evaluated by alkaline phosphatase staining, alizarin red staining, and RT-PCR. ALP staining was performed with a BCIP / NBT alkaline phosphatase staining kit (Beyotime, China). In short, a 6-well plate of MC3T3-E1 induced for 7 days was fixed with 95% ethanol, rinsed with PBS buffer, and treated with 500 μL of dye. The cells were then washed with water and imaged with an Olympus microscope and EPSON scanner. For Alizarin Red S (ARS) staining, cells were preserved in 95% ethanol for 15 minutes after 14 days of osteogenic induction. The cells were then gently rinsed three times with PBS buffer and stained with 1% Alizarin Red S (pH = 4.2, Solarbio, China) for 5 minutes. Finally, the unbound dye was gently washed off the cell surface with PBS buffer. Under an inverted microscope, the cells were examined for orange-red mineralized nodules and recorded. To determine the expression of osteogenesis-related genes, RT-PCR was used to detect the expression levels of RUNX family transcription factor 2 (Runx2), alkaline phosphatase (ALP), osteocalcin (OCN), osteoprotein (OPN) and osteoblast-specific genes (Osterix). After 7 and 14 days of osteogenic induction, total RNA of the cells was extracted using the Mini BEST Universal RNA Extraction Kit (TaKaRa, Japan) and the concentration was measured. Reverse transcription was performed using the Prime Script RT Kit (TaKaRa, Japan). The cDNA template was amplified using TB Green Premix Ex Taq II RT-PCR (TaKaRa, Japan). GAPDH was used as an internal reference control. The primer sequences used for PCR amplification are shown in Table 1. RT-PCR was performed by using the Light Cycler / Light Cycler 480 system (Roche, Switzerland). Relative mRNA expression was calculated using the 2-ΔΔCt method, and each analysis included 3 to 5 replicates. Fig. 9 shown.
[0100] Table 1 Primer sequences
[0101] Gene Forward primer (5'→3') Reverse primer (3'→5') RUNX2 CCGAAATGCCTCCGCTGTTATG GGATTTGTGAAGACTGTTATGGT ALP TATGTCTGGAACCGCACTGAAC CACTAGCAAGAAGAAGCCTTTGG OCN GGTGCAGACCTAGCAGACACCA AGGTAGCGCCGGAGTCTATTCA OPN AGCAAGAAACTCTTCCAAGCAA GTGAGATTCGTCAGATTCATCCG Osterix CGTCCTCTCTGCTTGAGGAA TTTCCCAGGGCTGTTGAGTC GAPDH CAGCAACTCCCACTCTTC TGTAGCCGTATTCATTGTC
[0102] The ideal osteogenic biomaterial should effectively promote the osteogenic differentiation of cells and have strong biocompatibility. The osteogenic induction ability of GelMA / HAMA-OGP hydrogel scaffolds was evaluated by ALP staining, ARS staining and RT-PCR. ALP activity can be used as an early marker of cell osteogenic differentiation. For the ALP staining results, positive staining results were observed in all groups. It is worth noting that the GelMA / HAMA-OGP hydrogel group showed more positive staining results on day 7 compared with the control group and the GelMA / HAMA hydrogel group. After 14 days of co-culture with the hydrogel, MC3T3-E1 cells were stained with Alizarin red to show the development of calcified nodules, which is a phenotypic marker of late osteogenic differentiation, indicating the ability of late osteogenic differentiation. The results showed that the blank group had tiny dark red nodules. The GelMA / HAMA group in the control group showed an increase in red nodules, however, the overall number was not significant. A large number of red mineralized nodes and strong red positive reactions were seen in the GelMA / HAMA-OGP hydrogel group. To further explore the osteogenic differentiation of MC3T3-E1 cells in different samples, RT-PCR was used to detect the gene expression of osteogenic-related proteins after 7 and 14 days of induction of osteogenesis, including ALP (an early marker of osteogenic differentiation), Runt-related transcription factor 2 (RUNX2, a central regulator of osteoblast differentiation), osteocalcin (OCN, a regulator of Ca 2+ Balance and bone mineralization, as a marker of the stage of bone mineralization), OPN (the main non-collagenous component of bone), and Osterix (a transcription factor related to osteoblast differentiation and bone formation). Compared with the other groups, the expression of five genes related to osteogenic differentiation was upregulated in the GelMA / HAMA-OGP group (*p<0.05, **p<0.01, ***p<0.001, ****p<0.0001), confirming its osteogenic activity. In conclusion, the GelMA / HAMA-OGP group enhanced the osteogenic ability of MC3T3-E1 cells in vitro and is a promising scaffold material for promoting osteogenic differentiation.
[0103] In vivo testing
[0104] Eight-week-old male SD rats were anesthetized and had femoral defects. The composite hydrogel was injected into the bone defect area of the rats. The rats were killed 8 weeks later, and the samples were collected, fixed, paraffin-embedded, and sliced for Masson staining. Fig.10 As shown. Blue indicates newly formed bone, and red indicates mature bone tissue. It can be clearly seen in the figure that the bone defects treated in the experimental group were replaced by lamellar bone and bone marrow, and some areas of the bone were highly mature. Masson staining showed that the composite hydrogel can significantly promote bone regeneration in the femoral defect area of rats.
[0105] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. An injectable photocurable composite hydrogel, characterized in that: The composite hydrogel is obtained by mixing methacrylylated gelatin and methacrylylated hyaluronic acid and then irradiating the mixture with blue light.
2. The composite hydrogel according to claim 1, characterized in that The mass ratio of the methacryloyl gelatin to the methacryloyl hyaluronic acid is 1-10:
1.
3. An injectable photocurable OGP-loaded composite hydrogel, characterized in that: The OGP-loaded composite hydrogel comprises the composite hydrogel according to claim 1 and OGP, wherein the OGP is graft-copolymerized in the composite hydrogel by photo-crosslinking.
4. The method for preparing the composite hydrogel according to claim 1, characterized in that: The preparation method comprises the following steps: i) dissolving methacryloyl gelatin (GelMA) and methacryloyl hyaluronic acid (HAMA) in deionized water or phosphate buffer containing lithium acylphosphonate (LAP) to obtain a GelMA / HAMA mixed solution; ii) using blue light to irradiate the GelMA / HAMA mixed solution to obtain the composite hydrogel.
5. The method for preparing the OGP-loaded composite hydrogel according to claim 3, wherein: The preparation method comprises the following steps: a) dissolving methacryloyl gelatin (GelMA) and methacryloyl hyaluronic acid (HAMA) in deionized water or phosphate buffer containing lithium acylphosphonate (LAP) to obtain a GelMA / HAMA mixed solution; b) mixing the GelMA / HAMA mixed solution with the osteogenic growth peptide OGP, and stirring in a dark environment to obtain a composite hydrogel precursor; ii) using blue light to irradiate the composite hydrogel precursor to obtain the OGP-loaded composite hydrogel.
6. The preparation method according to claim 4 or 5, characterized in that: In step i, the concentration of the GelMA solution is 1wt%-20wt%, the concentration of the HAMA solution is 0.5wt%-10wt%, and the concentration of the LAP is 0.05wt%-1wt%.
7. The preparation method according to claim 5, characterized in that: The OGP concentration is 0.01wt%-0.2wt%.
8. The preparation method according to claim 4 or 5, characterized in that: The wavelength of blue light is 400-450nm, and the cross-linking time is 10-50 seconds.
9. The use of the composite hydrogel according to claim 1, characterized in that: Used for preparing cell culture carriers, drug carriers or bone repair materials.
10. The use of the OGP-loaded composite hydrogel according to claim 3, characterized in that: Used to prepare bone repair materials.
Citation Information
Cited By
Composite hydrogel stent as well as preparation method and application thereof
CN121154925A